ANALISIS PENDAPAT MAHASISWA FKIP PASCA MAGANG DALAM PENERAPAN KOMPETENSI SOSIAL GURU DI SEKOLAH - Muhammad Roshoof S. Faros Kaab; Yanto; Dinny Rahmmayanty (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
This study aims to analyze the application of social competencies by FKIP students after completing their teaching internships and its impact on learning success. Social competencies, which include communication skills, teamwork, sympathetic interaction, and a pleasant demeanor, are crucial for fostering effective relationships between teachers, students, and the surrounding community while supporting the creation of a conducive learning environment. The findings indicate that strong communication skills improve teacher-student relationships, while effective collaboration among teachers and educational staff creates a productive environment. Additionally, sympathetic interaction and a pleasant demeanor were found to promote a harmonious classroom atmosphere and motivate students. Based on these findings, it is recommended that prospective teachers develop strong communication skills, enhance collaboration among educators, and improve their ability to interact sympathetically while maintaining a friendly, enthusiastic, and optimistic attitude to create more effective and enjoyable learning experiences for students.